2014
DOI: 10.4236/cweee.2014.32006
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy Sustainability in Jordan

Abstract: Jordan is a country with highly fossil fuel deficiency and thus other energy sources are needed to be explored. Solar energy in Jordan is highly recognized as a good source of energy and an excellent substitute to the fossil fuel. The solar energy in this article is obtained via data bases and modeling techniques for the specified place coordinate and angle of inclination. The angles of sun irradiations are different throughout the year; therefore solar energy needs to be magnified by optimizing the angle of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The contribution of solar energy to the total energy for the years 2002 and 2007 was estimated in [109]. The results showed that solar energy contributed around 1.2-1.7% in 2002 and that this rate increased up to 2.1% in 2007.…”
Section: Jordanmentioning
confidence: 99%
“…The contribution of solar energy to the total energy for the years 2002 and 2007 was estimated in [109]. The results showed that solar energy contributed around 1.2-1.7% in 2002 and that this rate increased up to 2.1% in 2007.…”
Section: Jordanmentioning
confidence: 99%
“…2 Cedars hotel buildings Fig. 3 Average number of sun hours per month in Jordan [50] celebration hall, corridors, restaurant and reception were estimated to be 50,457 kWh per month. Table 2 presents the total estimated monthly load of the hotel (77,099 kWh).…”
Section: Electrical Load Estimation Of the Hotelmentioning
confidence: 99%
“…Therefore, reassessing policies towards more secure energy has become one of the main political issues in Jordan. In order to make sure that the transition to sustainable energy is reliable, affordable, and realistic, there is a need to focus on its diversification and import reduction, as well as increased dependence on renewable energy sources [5][6][7][8][9][10][11][12]. Jordan started looking for options and working on investment in oil shale, which positions Jordan fifth in the world in oil shale reserves.…”
Section: Introduction 1energy In the World And Jordanmentioning
confidence: 99%